Controle da temperatura de um biorreator com ordem fracionária utilizado na produção de álcool - Inacio, Danilo (2021)
Several environmental impacts are associated with the high consumption of fossil fuels. The global energy matrix is composed mostly of non-renewable sources, this dependence related to the intense use and unbridled exploitation of these natural resources, causes the levels of reservoirs to decrease more and more. In this scenario, alcohol emerges as a sustainable alternative energy source, being seen as positive in environmental issues, as it is a renewable substance. The main form used in the production of alcohol is fermentation by the yeast Saccharomyces cerevisiae in a continuously stirred tank bioreactor, CSTR - Continuous Stirred-Tank Reactor. An important variable for this microorganism is temperature, and its optimum point for alcohol production is 32°C. The dynamic analysis of the process was performed for the system without temperature control of the bioreactor and with temperature control by water flow in the jacket to control the coolant flow. Furthermore, it is proposed to consider the heat exchange between the bioreactor and the jacket through heat conduction in fractional order. In open loop, the fermentation bioreactor takes time to stabilize its process, at this point, the stabilization temperature is approximately 36°C. Thus, a control system is needed to keep the bioreactor at the ideal fermentation temperature. The chosen strategy was the LQR - Quadratic Linear Regulator, as it is a simple and robust control technique. After performing the closed-loop bioreactor simulations by inserting an oscillatory input considering a time-varying temperature function Tin(t), it was possible to verify that the bioreactor had a satisfactory operational performance, quickly and efficiently controlling the temperature within the range acceptable from 2% to 5% of controller setpoint value.